Modern trends in documentation : proceedings of a symposium held at the University of Southern California, April 1958 - Boaz, Martha Terosse (London, New York, Pergamon Press, 1959)
In trying to organize information for a better storage and retrieval, the School of Library Science of the University of Southern California organized a symposium. Papers presented by various persons are contained in this book.
Bibliographical footnotes.
gp. 21/01/2019
Loans
Keywords: Information storage and retrieval systems; Information retrieval; Documentation